STUDI KASUS: KONSELING KELOMPOK CLIENT-CENTERED DALAM MENGURANGI PERILAKU MEMBOLOS EKSTRAKURIKULER PRAMUKA PADA SISWA KELAS IX MTsN 2 SURABAYA - Sutanto, Tiara Putri; Purwoko, Budi (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
The behavior of skipping compulsory extracurricular classes at school is a phenomenon that often occurs, especially truant in scout extracurricular activities. This behavior can negatively impact student participation and learning experience in scout activities. Truant behavior can be reduced little by little through one of the counseling approaches, namely client-centered, this article aims to identify client-centered counseling approaches that are effective in reducing scout truant behavior carried out at State Islamic Junior High School 2 Surabaya. The method used is descriptive field research with a case study design. The subjects in this study were four class IX-C students who indicated truant behavior in high scouts at State Islamic Junior High School 2 Surabaya. Data collection was carried out using observation, interview and documentation techniques. The results of this study concluded that the provision of client-centered group counseling services was quite effective in reducing the truant behavior of scouts. The author conducted interviews first before identifying the provision of client-centered group counseling services carried out by guidance and counseling teachers or counselors to grade IX-C students at State Islamic Junior High School 2 Surabaya.